An alteration in ATG16L1 stability in Crohn disease - Lassen, Kara G (Landes Bioscience, 2014)
Individuals who harbor a common coding polymorphism (Thr300Ala) within a structurally unclassified region of ATG16L1 are at increased risk for the development of Crohn disease. Recently, we reported on the generation and characterization of knockin mice carrying the ATG16L1 T300A variant. We demonstrate that multiple cell types from T300A knock-in mice exhibit reduced selective autophagy, and we mechanistically link this phenotype with an increased susceptibility of ATG16L1 T300A to CASP3- and CASP7-mediated cleavage. These findings demonstrate how a single polymorphism can result in cell type- and pathway-specific disruptions of selective autophagy and alterations in the inflammatory milieu that can contribute to disease.